Firm's readiness to internationalization / Herwina Rosnan ... [et al.] - Rosnan, Herwina; Chua Abdullah, Nuraisyah; Yusof, Norzayana; Abdullah, Muhammad Syukri (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2018)
This study addresses primary issues on the internationalization readiness among Small and Medium Enterprises (SMEs). Four factors namely foreign distributing, foreign marketing, foreign network and entry strategy are examined to help in enhancing the understanding on internationalization readiness among SMEs. The main purpose of this paper is to examine the impact of these exogenous variables on internationalization readiness among SMEs in Malaysia. The methodology utilizes primary data from questionnaires which were administered to a sample of 190 SMEs in Malaysia. These self-administered questionnaires were distributed using the non-probability sampling technique which is purposive sampling technique. Descriptive statistics, Internal Consistency - Composite Reliability (CR), Indicator Reliability – Indicator Loadings, Average Variance Extracted (AVE) (Convergent Validity), Fornell Larcker Criterion Discriminant Validity), Standard Beta, T-value, Effect Size (f2) and R Square were employed. Analysis method was performed by using Smart Partial Least Square (SmartPLS) path model analysis. The results show that all factors were significantly correlated to Internationalization Readiness. Further, this paper offers discussions and conclusions.